APLIKASI FOTOGRAMETRI JARAK DEKAT UNTUK PEMODELAN 3D CANDI GEDONGSONGO - Akhmad Didik Prastyo; Sawitri Subiyanto; Andri Suprayogi (Departement Teknik Geodesi Universitas Diponegoro, 2012)
Close range photogrammetry is a one of photogrammetry applications. It can be used for the object measurement that is less than 100 meters. It also usualy used in 3D modeling of buildings, vehicles or bridges. In this final task, close range photogrammetry method was used for 3D modeling of 1st temple in Gedong Songo Temple using non-metric digital camera. Initially, the camera must through of calibration process to determine the camera internal parameters. The process of calibration and data processing in this final task are using PhotoModeler Scanner v.6 software. Phase of buildings modeling contain of marking and referencing, calculating and 3D modeling, transformation of 3D coordinate and visualization of 3D models. The final results in this research is 3D model of 1st Temple in Gedong Songo Temple. Testing of the results in 3D modelling processing was done by comparing the 3D model coordinates refernced to Electronic Total Station measurement and comparison with the distance of the measuring tape. The average value of the ratio of the coordinate error is 0.087 meters and the average distance error of comparison with the measuring tape is 0.099 meters. Keyword: Close range photogrammetry, Building Modeling, Temple, Non-Metric Digital Camera, PhotoModeler Scanner V.6.